Revision of the ocellatus species-group of the genus Plumarius Philippi 1873 (Hymenoptera, Chrysidoidea, Plumariidae), with description of three new species from Argentina - Diez, Patricia Alejandra (2013)
This contribution presents the study of species-group of Plumarius Philippi 1873, as the result of a survey of the morphological variation in males. The group is characterized by the large ocelli and transverse head. It consists of the following three new species: P. culminatus Diez, Fidalgo & Roig-Alsina, sp. nov., P. ocellatus Diez, Fidalgo & Roig-Alsina, sp. nov., and P. stangei Diez, Fidalgo & Roig-Alsina, sp. nov. A characterization of the group, descriptions, and illustrations are provided.